Subculture Identity in the Use of Foreignization as Translanguaging Strategy in X - Irmala Sukendra (Journal of Language and Literature, 2026)
This study aims to find the construction of foreignization as translanguaging strategy in X and whether this strategy acts as a means of communication to project the translingual identity as members of a Kpop fans subculture group. Methodologically, this study adopted a netnographic study concentrating on the lurking method.  X posts (tweets) from native Indonesian speakers of a Kpop fans subculture group, dated or posted from June 2023 to September 2024 are obtained as the source of data. Following data collection, the findings were analysed and contextualized using established theoretical frameworks, employing qualitative analysis to examine data from similar incidents. This study found that by embracing translanguaging as a means of projecting a translingual identity, individuals navigate the complexities of subculture group membership and foster inclusive communities within the digital realm. The study showed that the group members used foreignization as their translanguaging negotiation strategy which is formulated similarly to L2 word formation and sentence construction. They blended the words from L2 (English) with words/morphemes from L1 (Indonesian) and formed words by adding L1 affixes to L2 or L3 (Korean) words with the pronunciation written  in L1. Through employing this strategy, they attract other interlocutors who share similar interests. The identities they projected in their communications in X interactions can be said as the identity as the member of the subculture groups.